Arp2/3-dependent regulation of ciliogenesis governs adaptive distal tubular epithelial cell states in kidney disease - Rogg, Manuel; Weißer, Lisa; Maier, Jasmin I.; Sigle, August; Helmstädter, Martin; Stigler, Marlene; Sammarco, Alena; Gräwe, Katja; Andreev, Grigor; Kark, Charlotte; Ramakrishnan, Suresh Krishna; Özel, Cem; et al. (Science advances, 2025)
Proteinuric kidney disease substantially affects renal tubules through incompletely understood mechanisms. We identify elongation of primary cilia in distal renal tubules in the context of glomerular nephropathy. In renal biopsies and mouse models, tubular injury correlates with ciliary elongation, tubule dilation, and disruption of the cortical actin cytoskeleton. In vitro studies implicate biophysical cues of the glomerular filtrate and subsequent dysregulation of the actin cytoskeleton as contributing factors, confirmed by conditional deletion of N-WASP and Arp2/3 in vivo and in vitro. Electron and fluorescence microscopy revealed enlarged ciliary pockets, basal body mislocalization, and intracellular cilia formation in Arp3 knockout conditions. Transcriptome analysis identifies the essential role of cilia in maintaining adaptive tubular cell states, while persistent activation leads to disease progression through extracellular matrix remodeling, exemplified by Tenascin-C. Our findings establish cilia as central mediators of tubular adaptation to injury and identify the Arp2/3-dependent actin cytoskeleton as a critical regulator, providing essential insights into the pathogenesis of chronic kidney disease.
Veröffentlicht: 28. November 2025
Gesehen am 27.02.2026